Analisis Komparatif Pemantauan Kualitas Udara Ambien di Surabaya Pada Tahun 2023 - Fajar Shufi Fauzianto; Munawar Ali (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2024)
This research aims to analyze ambient air quality in the city of Surabaya, with a focus on four main locations: industry, transportation, offices and residential areas during two different periods, the dry season and the rainy season in 2023. This analysis is important for assessing the influence of urbanization and industrial activity. to the environment and public health. The method used is descriptive and comparative observational, where measurements are made of main pollutant parameters such as SO2, CO, NO2, O3, Pb, NMHC, PM10, PM2.5, and TSP. Sampling was carried out twice at each location, in accordance with SNI 19-7119.6-2005 and PPRI No. 22 of 2021 standards. The research results showed that the concentrations of all pollutants were below the specified threshold, indicating the effectiveness of existing air control policies. However, there are differences in pollutant concentrations between locations and significant seasonal changes, requiring more dynamic and tailored pollution management strategies. The study's conclusions suggest the importance of continuous monitoring, increased green space, public education about pollution, as well as stricter policies to control pollutant emissions. This research provides valuable empirical data for policy makers to develop effective strategies for managing air quality and reducing health risks in Surabaya..